Why farmers use so many different maize varieties in West Kenya. (December 2021) - Almekinders, Conny J.M.; Hebinck, Paul; Marinus, Wytze; Kiaka, Richard D.; Waswa, Wycliffe W.
In this article we reflect on the discussions as to whether breeding and seed system development should proceed along its current well established route of developing varieties with a higher agricultural productivity or if the diversity of farmers, their contexts and rationales requires broader approaches. We make use of data from a recently held survey (2018) in West Kenya. The data show that some 80% of the households in the survey planted both local and hybrid maize varieties. The choices that people make about which variety to plant are many. Apart from rainfall, the availability of cash, the promise of a good yield, the presence of projects and programs and the culture of seed also influences these choices. We argue that an inclusive demand-oriented maize breeding and seed system needs to include a range of varieties and seed sources and to develop and support different delivery pathways to fit farmers' diverse use of seeds and varieties. Our findings also indicate the need for more systematic study of the diversity of farmers' rationales and the performance of crop varieties. This would provide useful information for all the actors involved.